Comparison of the Results of a Parkinson's Holter Monitor With Patient Diaries, in Real Conditions of Use: A Sub-analysis of the MoMoPa-EC Clinical Trial - Pérez-López, Carlos; Hernández-Vara, Jorge; Caballol, Nuria; Bayes, Àngels; Buongiorno, Mariateresa; Lopez-Ariztegui, Núria; Gironell, Alexandre; López-Sánchez, José; Martínez-Castrillo, Juan Carlos; Sauco M, Alvarez; López-Manzanares, Lydia; Escalante-Arroyo, Sonia; et al. (Frontiers in Neurology, 2022)
Background: For specialists in charge of Parkinson's disease (PD), one of the most time-consuming tasks of the consultations is the assessment of symptoms and motor fluctuations. This task is complex and is usually based on the information provided by the patients themselves, which in most cases is complex and biased. In recent times, different tools have appeared on the market that allow automatic ambulatory monitoring. The MoMoPa-EC clinical trial (NCT04176302) investigates the effect of one of these tools - Sense4Care's STAT-ON - can have on routine clinical practice. In this sub-analysis the agreement between the Hauser diaries and the STAT-ON sensor is analyzed. Methods: 84 patients from MoMoPa-EC cohort were included in this sub-analysis. The intraclass correlation coefficient was calculated between the patient diary entries and the sensor data. Results: The intraclass correlation coefficient of both methods was 0.57 (95% CI: 0.3-0.73) for the OFF time (%), 0.48 (95% CI: 0.17- 0.68) for the time in ON (%), and 0.65 (95% CI%: 0.44-0.78) for the time with dyskinesias (%). Furthermore, the Spearman correlations with the UPDRS scale have been analyzed for different parameters of the two methods. The maximum correlation found was -0.63 (p<0.001) between Mean Fluidity (one of the variables offered by the STAT-dON) and factor 1 of the UPDRS. Conclusions: This sub-analysis shows a moderate concordance between the two tools, it is clearly appreciated that the correlation between the different UPDRS indices is better with the STAT-ON than with the Hauser diary.